Weather radar observations of the Hekla 2000 eruption cloud, Iceland - Lacasse, C.; Karlsdóttir, S.; Larsen, G.; Soosalu, H.; Rose, W. I.; Ernst, G. G.J. (Bulletin of Volcanology, 2004)
The Hekla eruption cloud on 26-27 February 2000 was the first volcanic cloud to be continuously and completely monitored advecting above Iceland, using the C-band weather radar near the Keflavík international airport. Real-time radar observations of the onset, advection, and waning of the eruption cloud were studied using time series of PPI (plan-position indicator) radar images, including VMI normal, Echotop, and Cappi level 2 displays. The reflectivity of the entire volcanic cloud ranges from 0 to > 60 dBz. The eruption column above the vent is essentially characterised by VMI normal and Cappi level 2 values, > 30 dBz, due to the dominant influence of lapilli and ash (tephra) on the overall reflected signal. The cloud generated by the column was advected downwind to the north-northeast. It is characterised by values between 0 and 30 dBz, and the persistence of these reflections likely result from continuing water condensation and freezing on ash particles. Echotop radar images of the eruption onset document a rapid ascent of the plume head with a mean velocity of ∼30 to 50 m s-1, before it reached an altitude of ∼11-12 km. The evolution of the reflected cloud was studied from the area change in pixels of its highly reflected portions, > 30 dBz, and tied to recorded volcanic tremor amplitudes. The synchronous initial variation of both radar and seismic signals documents the abrupt increase in tephra emission and magma discharge rate from 18:20 to 19:00 UTC on 26 February. From 19:00 the > 45 dBz and 30-45 dBz portions of the reflected cloud decrease and disappear at about 7 and 10.5 h, respectively, after the eruption began, indicating the end of the decaying explosive phase. The advection and extent of the reflected eruption cloud were compared with eyewitness accounts of tephra fall onset and the measured mass of tephra deposited on the ground during the first 12 h. Differences in the deposit map and volcanic cloud radar map are due to the fact that the greater part of the deposit originates by ...